2021
DOI: 10.1007/s40888-021-00225-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of public loans in financing business R&D through the economic cycle

Abstract: Should governments increase their efforts in R&D public funding during recession periods? The objective of the present study is to compare the effect of public aid to business R&D on technological inputs and outputs through the economic cycle. We contribute to this literature by examining the effect of one specific instrument of direct public support: selective loans for firms' R&D projects. For the analysis, we consider Spanish firms supported through this kind of instrument for the periods 2002-2005 and 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…While, the economic crisis of 2008 is very different from the contemporary crisis caused by the COVID-19 pandemic, the lessons learned from previous crises do, however, provide useful benchmarks when designating policy actions to mitigate the negative impacts of the contemporary one. The responses to tackling the COVID-19 pandemic indicate that governments have, at least partly, recognized that one of the best instruments for surviving and recovering from crises are related to supporting RDI (Barajas et al, 2021). In fact, several countries have included RDI policies into their efforts in tackling the negative effects of the COVID-19 pandemic (Braunerhjelm, 2022).…”
Section: Rdi Funding and Regional Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…While, the economic crisis of 2008 is very different from the contemporary crisis caused by the COVID-19 pandemic, the lessons learned from previous crises do, however, provide useful benchmarks when designating policy actions to mitigate the negative impacts of the contemporary one. The responses to tackling the COVID-19 pandemic indicate that governments have, at least partly, recognized that one of the best instruments for surviving and recovering from crises are related to supporting RDI (Barajas et al, 2021). In fact, several countries have included RDI policies into their efforts in tackling the negative effects of the COVID-19 pandemic (Braunerhjelm, 2022).…”
Section: Rdi Funding and Regional Growthmentioning
confidence: 99%
“…It was seen that the money would have been better spent for the direct support of firms that were the most affected by the crisis (National Audit Office of Finland, 2021). However, the economic crisis of 2008 showed that the public support to firms with the best ideas and the most business growth potential may, in fact, be a better way to boost the economy (Barajas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%